Wacana Kritis Normal Fairclough Berita Media Massa Daring: Jepang Buang Limbah Nuklir - Khosnol Khotimah; Khusnul Khotimah (PRASASTI: Journal of Linguistics, 2024)
This research aims to critically explain an event, analyze discourse, and identify crucial elements in the event of Japan disposing nuclear waste into the sea. The data source for this study comprises news articles on Japan's disposal of nuclear waste from five different online mass media outlets: CNN Indonesia, Detik.com, Liputan6.com, Kompas.com, and CNBC Indonesia. The research employs a qualitative descriptive research method using observation and note-taking techniques. The news articles are analyzed using Norman Fairclough's AWK, which includes three dimensions: microstructural, mesostructural, and macrostructural. The analysis results indicate that in the news articles, there is a microstructural dimension reflected in the use of almost identical vocabulary, specifically "Japan Dumps Nuclear Waste into the Sea," which forms the core of the information discussion. The mesostructural dimension reveals that each media outlet has a different focus in their news coverage. In the macrostructural dimension, the news is also related to the increasingly worrisome situation and the financial decline of Japan, and it makes reference to a Japanese Corporate Institution. The implications of this research underscore the importance of how the media shapes public perception, the significant impact of news coverage on opinions and economic stability, the integral role of corporate institutions in framing events, the heightened awareness of environmental issues, and the criticism of the uniformity in media coverage, all of which can influence public views and policies.